The Involvement In Tunas Niaga Activities And The Entrepreneurial Attitude Among Secondary Schools - Yap Kwee Leng; Nor Aishah Buang (Universitas Muhammadiyah Surakarta, 2019)
The purpose of this study is to identify the involvement in Tunas Niaga activities and the entrepreneurial attitude among secondary school. The involvement of entrepreneurial activity among students is an important component of forming entrepreneurial attitudes. However, entrepreneurial activity is less favored by high school students. Most high school students perceive entrepreneurship, tediousness and do not guarantee future lives during economic problems.Lacking the problem, a study was conducted to examine the level of involvement of entrepreneurial activity and entrepreneurial behavior. The study uses survey method with questionnaire as the first instrument. The instruments is adapted from Khalina Khalid (1991) to construct the basic information of entrepreneurship activities as well as the construct of entrepreneurial attitude adapted from Ravi and Aishah Buang's instrument (2015) psychometric index of entrepreneurship.The sample of the study consists of 30 secondary school students taken randomly involving entrepreneurship activities such as Tunas Niaga.The results of the analysis of entrepreneurial entrepreneurship activity confirmed two constructs involving entrepreneurial activity with Cronbach Alpha's reliability and reliability value of .714. The dimensions of entrepreneurship showed that Cronbach Alpha .900. The min test results show the level of involvement of moderate entrepreneurship activities. Entrepreneurship attitude among respondents shows positive towards entrepreneurship activity.